The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2004
DOI: 10.1097/00129492-200405000-00021
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, Experimental, and Theoretical Investigations of the Effect of Superior Semicircular Canal Dehiscence on Hearing Mechanisms

Abstract: The results suggest that superior semicircular canal dehiscence can affect hearing function by introducing a third window into the inner ear.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
233
4
7

Year Published

2005
2005
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 254 publications
(257 citation statements)
references
References 17 publications
13
233
4
7
Order By: Relevance
“…Air-conducted sound causes a stapes volume velocity, which is partially shunted through the superior semicircular canal when there is a dehiscence. This shunting leads to a decrease in the stimulus to the cochlea and diminishes the round window velocity (adapted from Rosowski et al, 2004). Table 1 The mean, SD (column 2) and significance (column 3) of the dB difference of the cochlear potential magnitude between the intact (pre-SCD) condition and after the introduction of the dehiscence (post-SCD) (n = 11) NS NS denotes cases where the null hypothesis that the manipulations do not alter the CP is accepted at the 5% significance level.…”
Section: Mechanism Of Decreased Sensitivity To Ac Stimulimentioning
confidence: 99%
See 2 more Smart Citations
“…Air-conducted sound causes a stapes volume velocity, which is partially shunted through the superior semicircular canal when there is a dehiscence. This shunting leads to a decrease in the stimulus to the cochlea and diminishes the round window velocity (adapted from Rosowski et al, 2004). Table 1 The mean, SD (column 2) and significance (column 3) of the dB difference of the cochlear potential magnitude between the intact (pre-SCD) condition and after the introduction of the dehiscence (post-SCD) (n = 11) NS NS denotes cases where the null hypothesis that the manipulations do not alter the CP is accepted at the 5% significance level.…”
Section: Mechanism Of Decreased Sensitivity To Ac Stimulimentioning
confidence: 99%
“…Previous reports have investigated the role of SCDs on auditory sensitivity in response to boneconducted (BC) sound stimuli in an animal model Rosowski et al, 2004;Sohmer et al, 2004). These studies demonstrated that sensitivity to BC stimuli increases after the introduction of a dehiscence and that the increase is greatest at frequencies below 2 kHz .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Here, 'x' represents the length of the BM from the stapes. For example, P a (5) indicates that the P a at the position of 5 mm from the base of the BM.…”
Section: Anti-symmetric Pressurementioning
confidence: 99%
“…Therefore, a third window (TW), which is another fluid pathway in the cochlea except the OW and RW, was suggested as a possibile factor to explain the asymmetry of the volume velocity ratio. However, in spite of many studies for potential TWs [1,4,5], it is still unclear which opening in the real cochlea acts as the TW causing the asymmetry of the ratio. In order to further investigate the effect of the TWs on the asymmetry of the volume velocity ratio, we used a 3-D finite-element (FE) human-ear model consisting of the middle ear and the cochlea.…”
Section: Introductionmentioning
confidence: 99%